5PSQ-098 Analysis of gastrostomy catheters replacement in at-home patients. (2nd March 2018) - Garcia, D; Jimenez, B; Ripa, C; Sola, A; Gayan, M; Leunda, L; Zurutuza, A; Urretavizkaia, M; Landa, J; Bachiller, M
Abstract : Background: Percutaneous radiologic gastrostomy (PRG) consists of inserting a long-term catheter in the gastric cavity through the anterior abdominal wall. The catheter is replaced every 6 months (180 days). However, it can often require a replacement in advance due to obstruction or bad management of the catheter. Purpose: To analyse the most common causes of PRG replacement and its frequency. Material and methods: An observational retrospective study was conducted. All patients with PRG were included. Also analysed was PRG indication, number of replacements and its causes, the average duration of catheter placement and the reason of removing it. All the data havw been collected from electronic medical records and have been processed through the Stata statistics program. Results: A total number of 63 patients that had a 16 Fr catheter in place were included; 42 were males and 21 females with a mean age of 65.5±11.8. The median follow-up was 113 days. PRG indications were: 46% (29) head and neck tumour, 17.5% (11) amyotrophic lateral sclerosis (ALS), 16% (10) cerebrovascular accident, 1.5% (one) dementia and 19% (12) others. Ninety-four catheters were replaced, from which 79% (74) were not programmed due to: 34% (32) catheter came out, 17% (16) broken catheter, 9.5% (nine) medicines obstruction, 5.5% (five) obstruction due to liquid diet, 3.5% (three) leak, 1% (one) infected stoma and 8.5% (eight) others. The average duration of PRG before being replaced was 205±190 days in those patients that were programmed, whereas 78±66 days in those non-programmed. The average duration for a gastrostomy was 170 days. Results vary depending on the pathology: 263±164 days for ALS, 173±179 days for head and neck tumour and 134±123 days for cerebrovascular accidents. In 52 patients the catheter was removed, due to recovery (32%) or death (68%). Conclusion: Only one-fifth of the catheter replacements were programmed. The most common causes were because they came out or they were broken. In order to prevent these complications it is necessary to develop standard operational procedures and patient information leaflets on catheter management by a multidisciplinary team including nursing, medical and pharmacy staff.